Perioperative management of upper tract urothelial carcinoma in the Nordic countries - Oedorf, Kimie; Haug, Erik Skaaheim; Liedberg, Fredrik; Järvinen, Riikka; Gudjonsson, Sigurdur; Boström, Peter J.; Jerlström, Tomas; Gudbrandsdottir, Gigja; Jensen, Jørgen Bjerggaard; Lam, Gitte Wrist (BioMed Central, 2025)
Background: Upper tract urothelial carcinoma (UTUC) is a rare malignancy, with typically only few new cases annually per urological department. Adherence to European association of urology (EAU) guidelines on UTUC in the Nordic countries is unknown. The objective of this survey was to examine the implementation of EAU guidelines, the perioperative management and organization of the treatment of UTUC in the Nordic countries.
Methods: The electronic survey was distributed to 93 hospitals in the Nordic countries performing radical nephroureterectomy (NU). The survey consisted of 57 main questions and data was collected between December 1st, 2021 and April 23rd, 2022.
Results: Overall response rate was 47/93 (67%) with a completion rate of 98%. Five out of the 6 examined subjects on diagnostic practice are applied by ≥ 72% of the participating centers. NU as treatment for high-risk UTUC is performed by 37/47 (79%), and 91% include a bladder cuff excision.
Conclusions: Adherence to EAU guidelines is high on diagnostic practice in the Nordic countries, whereas disease management is less coherent.